Ionic cluster effect in suppression on superconductivity in Ni- and Co-doped YBCO systems - Wang, Aihua; Wang, Xiaoxia; Cao, Yigang; Li, Xinli; Wang, Yongyong; Gao, Liming; Lu, Heqiang; Zhang, Jie; Li, Pinglin (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We adopted the x-ray diffraction, oxygen contents, positron annihilation technology as well as simulation methods to investigate systemically YBa2Cu3-x(Ni,Co)xO7-d (x = 0-0.5). The simulated results show that ions distribute in dispersive form in little doped concentration. As doped concentration increases, ions combine into clusters in the crystal lattice. The calculated results and oxygen contents, together with the impure phases and the local electron density ne, show the ionic cluster effect, which not only causes the local electron density to reach the saturation, but also suppress the superconductivity significantly.